Application of Spatial Regression in Employment Characteristics Modelling - Pośpiech, Ewa Katarzyna; Mastalerz-Kodzis, Adrianna (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The article analyses the employment characteristics. The employment rate was studied in selected regions of Europe, and subsequently, for selected variables: total population employed, women employed and men employed, classic econometric models were constructed and the necessity of including the spatial factor in the process of modelling was verified. The demographic variables and GDP per capita were chosen as explaining variables of the model. It was analysed whether including a spatial approach in the models would improve their quality. Two basic spatial models were taken into consideration: the spatial error model and the spatial lag model, the former of which turned out to be the right tool for the analyses.